Clinical Benefit of Pazopanib in a Patient with Metastatic Chondrosarcoma: A Case Report and Review of the Literature - Tsavaris, Onoufrios; Economopoulou, Panagiota; Kotsantis, Ioannis; Reppas, Lazaros; Avgerinou, Chrysanthi; Spathas, Nikolaos; Prevezanou, Maria; Psyrri, Amanda (Frontiers in Oncology, 2018)
Chondrosarcoma is a rare malignancy characterized by the production of cartilage matrix, displaying heterogeneous histopathology and clinical behavior. Due to lack of effective treatment for advanced disease, the clinical management of metastatic chondrosarcoma is exceptionally challenging. Chondrosardomas harbor molecular abnormalities, such as overexpression of platelet-derived growth factor receptor-alpha (PDGFRA) and PDGFR-beta (PDGFRB), which are required for cancer development, progression and metastasis. Pazopanib is a potent and selective multi-targeted tyrosine kinase inhibitor (TKI), which co-inhibits stem cell growth factor receptor (c-KIT), fibroblast growth factor receptor (FGFR,) PDGFR and vascular endothelial growth factor receptor (VEGFR) and has demonstrated clinical activity in patients with advanced previously treated soft tissue sarcoma (STS). Herein, we describe the unique case of a patient with metastatic chondrosarcoma who derived clinical benefit from pazopanib after first line chemotherapy failure.